Application of Heterotopic Transplantation of Cryopreserved Placenta Tissue in Combined Treatment of Women with Nervous System Dysfunction at Hypoestrogeny Background - Lutsenko, N. S.; Gritsaj, A. V.; Karpenko, V. G. (Problems of Cryobiology and Cryomedicine, 2004)
There were examined 62 women with dysfunction in nervous system on hypoestrogeny background. A comparative analysis of the efficiency of a combined treatment with cryopreserved placenta tissue (HTCPT) heterotopic transplantation and a traditional vascular therapy was carried out with studying the dynamics of subjective indices (in points) and the data of ultrasound Doppler scanning, hormonal and mediator homeostasis in patients under observation. The advantages of HTCPT in terms of correcting vegetative and psychoemotional disorders, estrogen concentration were noted. According to the data of investigation performed the HTCPT is a pathogenetically substantiated way for correcting the data of pathological states and can be used for cerebrovascular disease prevention.